The SKA view of the interplay between SF and AGN Activity, and its role in Galaxy evolution - McAlpine, K.; Prandoni, I.; Jarvis, M.; Seymour, Nick; Padovani, P.; Best, P.; Simpson, C.; Guidetti, D.; Murphy, E.; Huynh, M.; Vaccari, M.; White, S.; et al. (2014)
It has become apparent that active galactic nuclei (AGN) may have a significant impact on the growth and evolution of their host galaxies and vice versa but a detailed understanding of the interplay between these processes remains elusive. Deep radio surveys provide a powerful, obscuration-independent tool for measuring both star formation and AGN activity in high-redshift galaxies. Multiwavelength studies of deep radio fields show a composite population of star-forming galaxies and AGN, with the former dominating at the lowest flux densities (S1.4GHz<100~μJy). The sensitivity and resolution of the SKA will allow us to identify, and separately trace, the total star formation in the bulges of individual high-redshift galaxies, the related nuclear activity and any star formation occurring on larger scales within a disc. We will therefore gain a detailed picture of the apparently simultaneous development of stellar populations and black holes in the redshift range where both star-formation and AGN activity peak (1≤z≤4). In this chapter we discuss the role of the SKA in studying the connection between AGN activity and galaxy evolution, and the most critical technical requirements for such of studies